2021
DOI: 10.3390/ijerph18189818
|View full text |Cite
|
Sign up to set email alerts
|

Older Women’s Experiences of a Community-Led Walking Programme Using Activity Trackers

Abstract: Promoting physical activity amongst older adults represents a major public health goal and community-led exercise programmes present benefits in promoting active lifestyles. Commercial activity trackers potentially encourage positive behaviour change with respect to physical exercise. This qualitative study investigated the experiences and attitudes of older adults following a 6-week community-led walking programme utilising activity trackers. Eleven community-dwelling older women aged 60+ completed individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Two studies conducted exit interviews to collect this information, which could reveal useful feedback for intervention improvement. tracking, and whether one is more intrinsically or extrinsically motivated (45). It has also been found that some OA prefer competition (45), while others prefer collaboration (42) when engaging in physical activities.…”
Section: Flexibilitymentioning
confidence: 99%
See 3 more Smart Citations
“…Two studies conducted exit interviews to collect this information, which could reveal useful feedback for intervention improvement. tracking, and whether one is more intrinsically or extrinsically motivated (45). It has also been found that some OA prefer competition (45), while others prefer collaboration (42) when engaging in physical activities.…”
Section: Flexibilitymentioning
confidence: 99%
“…Three studies started the co-design based on a concept that researchers already drafted, for example, walking activity (38), social prescribing (47), and community displays (42). The stakeholders were involved to co-design the details of these concepts; three studies started without preconceived concepts from the researchers, used co-design to understand the challenges of the community, and interventions were then developed (39,47,48); one study helped the community to realise its own initiative, where the researchers positioned themselves as facilitators (45). As illustrated by the studies above, three levels of co-design emerged in our review.…”
Section: Collaborationmentioning
confidence: 99%
See 2 more Smart Citations
“…In the first category, even though OA are the end-users of an intervention, the intervention is co-designed among experts only (e.g., healthcare professionals), and tools have been developed to facilitate this kind of co-design (e.g., [ 16 ]). The second category includes studies that report interventions that are co-designed with OA, although there is no description of how the co-design was undertaken (e.g., [ 17 , 18 ]). The last category in the literature includes studies that report the details of how they engaged OA in the co-design or refer to the co-design methods applied (e.g., [ 19 , 20 , 21 , 22 ]).…”
Section: Introductionmentioning
confidence: 99%